AI Ethics and Risk in Indonesia’s Manufacturing Sector - Saputra, Brilian Adi (Sahabat Publikasi, 2025)
The manufacturing sector is a cornerstone of Indonesia’s economy, contributing substantially to GDP and employment. As manufacturers increasingly adopt artificial intelligence (AI) and related Industry 4.0 technologies, they face new ethical challenges and operational risks. This paper reviews the ethical implications of AI deployment in Indonesian manufacturing, examines risk management strategies and governance practices, and surveys relevant policy frameworks. Drawing on recent literature and reports, we identify key ethical concerns (such as worker displacement, algorithmic bias, data privacy, and safety) and explore how manufacturers can incorporate risk management (e.g., ISO 31000 and FMEA-based methods) to build trustworthy AI system. We also assess Indonesia’s national AI strategy and regulatory context (including the 2020–2045 AI National Strategy and recent Kominfo guidelines), noting strengths and gaps in current governance. The discussion synthesizes best practices for responsible AI use in manufacturing, and the conclusion offers recommendations for policymakers and industry, such as updating standards, investing in AI ethics and talent, and fostering multi-stakeholder oversight.